EDUKASI ASI EKSKLUSIF DAN IMPLEMENTASINYA BAGI IBU HAMIL DI RW 10 KELURAHAN PAMPANGAN XX KOTA PADANG - Vauline Basyir; Hudilla Rifa Karmia; Meilinda Agus; Ryskina Fatimah Siregar; Yulia Fauziah Amizuar; Eka Darmayanti Putri Siregar; Rionitara W ikarya; Intan Julianingsih; Sari Surahmi; Rahmi Andrita Yuda; Desmawati Desmawati; Aldina Ayunda Insani; et al. (Buletin Ilmiah Nagari Membangun)
World Health Organization reported 56 million babies, 34 million babies are not exclusively breastfed. Previous studies have shown 80% of them came from developing countries. The achievement of exclusive breastfeeding in Indonesia based on Indonesia Health Profile (2017) is 55.7% and decreased 54.0% in 2018. West Sumatera reached exclusive breastfeeding target 66.7% in 2017, but lower than Indonesia average target 80%. Babies are not exclusively breastfed are susceptible to morbidity and mortality. Exclusive breastfeeding has a role in preventing LBW, stunting, and reducing the risk of obesity and chronic disease. The lack of mother’s knowledge associated with the practice of exclusive breastfeeding Aims, to determine the knowledge in RW 10 Pampangan Nan XX Village. The assessment of knowledge about exclusive breastfeeding and overview of its implementation. The metode of this event was intervention an education exclusive brestfeeding for 14 pregnant women in RW 10, pampangan XX. Respondent was gave education on Whatsapp and Youtube. Data collection was got by questioners and interviews. The data was processed analyzed, after that was defined priority problems and made action of plans. Result, 78.6% of mothers knew about exclusive breastfeeding but only 43% implemented it. The causes of problem were incorrect about knowledge and techniques breastfeeding. The results of this study were submitted to the puskesmas and stakeholderfor advocacy. Hope that health promotif concerning axclusive breastfedding will increase, through of online and creative medias, by the same token will be escaleting sectoral collaboration as support.